The Effect of Group Counseling with Cognitive Defusion Technique in Cognitive Behavior Therapy to Enhance Self-Confidence - Miratul Mukaromah; Kus Hendar; Rina Mida Hayati (Grief and Trauma, 2025)
This research aims to examine the effect of Cognitive Behavior Therapy (CBT) group counseling using cognitive defusion techniques to increase students' self-confidence at Sunan Ampel Punggur Middle School. Adolescents' low self-confidence is a critical issue in education, considering that puberty is a sensitive period for forming self-concept. The decreasing self-confidence in junior high school students can be seen in withdrawn behavior, difficulty interacting socially, and the inability to express one's potential optimally. The research used a true-experimental design with a pretest-posttest control group design. From a population of 103 students, a sample of 14 students was selected through purposive sampling and divided into experimental and control groups. The experimental group received group counseling intervention for 6 meetings. The research instrument is a questionnaire with 19 items that have been tested for validity (rcount 0.499-0.612 > rtable 0.497) and reliability (Cronbach's Alpha X=0.850; Y=0.735). Data analysis used the Shapiro-Wilk normality test, Levene's Test of homogeneity, and paired sample t-test. Cognitive defusion techniques are focused on helping students not become over-identified with negative thoughts, allowing them to take a more objective perspective on internal experiences. The results showed a significant difference in the experimental group (t=16.644; p=0.000<0.05) with an increase in scores from 52.29 to 86.71, while the control group did not show a significant change (t=0.669; p=0.528>0.05). In conclusion, CBT group counseling with cognitive defusion techniques effectively increases junior high school students' self-confidence through mechanisms for separating themselves from negative thoughts, developing adaptive thinking patterns, and strengthening personal competence.